2018
DOI: 10.3233/npm-181746
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of stillbirth in Yemen

Abstract: This study identified many risk factors of stillbirth that are amenable to intervention. Encouraging women to deliver at health facilities, providing better management of obstetrical complications, proper antenatal care, and prompt referral services are essential for reduction of stillbirths in Yemen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…This study found that women who had labor length ≥24 h were three times more at risk to have fresh stillbirth compared to those having labor length <24 h. This finding is in agreement with similar study findings at Mizan Tepi Teaching Hospital, Ethiopia, 13 Bangladesh, 21 and Yemen, 17 which showed that labor length lasting submit your manuscript | www.dovepress.com…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found that women who had labor length ≥24 h were three times more at risk to have fresh stillbirth compared to those having labor length <24 h. This finding is in agreement with similar study findings at Mizan Tepi Teaching Hospital, Ethiopia, 13 Bangladesh, 21 and Yemen, 17 which showed that labor length lasting submit your manuscript | www.dovepress.com…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, it is also noted that women who started antenatal visits at the third trimester did not have enough time to complete the four antenatal follow-up visits or may not have benefited from all the basic antenatal care packages which can possibly prevent stillbirth. 17 Early antenatal care focusing on detection of complications has maximum benefits which can avert 21% of stillbirths. 18 WHO also recommends pregnant women to start the first antenatal visit in their first trimester or in the first four months of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 272 studies were included in our review and 95 studies met the criteria for inclusion in the meta‐analyses (Fig. ), while the remaining 177 studies are summarized in table format only. A summary of all studies included in the meta‐analyses is provided in Table S2 (online only).…”
Section: Resultsmentioning
confidence: 99%
“…The conflict, complex political geography, severe food insecurity, devastated economy and severity of the humanitarian crisis, however, compounded these challenges in Yemen, placing enormous strains on an already weak and fragmented health system. The confluence of ongoing large-scale conflict, infectious disease, and food insecurity in a country with endemic poverty and high prevalence of gender-based violence has placed women and children at increased risk of negative health outcomes, including unwanted pregnancy, obstetric complications and related mortalities and morbidities, and preventable maternal and child mortality [45,46].…”
Section: Discussionmentioning
confidence: 99%